Pengaruh Luas dan Status Penguasaan Lahan terhadap Profitabilitas dan Pendapatan Usahatani Padi Sawah di Subak Padanggalak Desa Kesiman Kertalangu Kota Denpasar - CALLISTA, DAVINA; BUDIASA, I WAYAN; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p11, 2022)
The Effect of Land Size and Ownership on Profitability and Income in Subak Padanggalak, Kesiman Kertalangu Village, Denpasar City Subak Padanggalak is located in Kesiman Kertalangu Village, Denpasar City and consists of 170 active farmers. These farmers can be categorized into low-income farmers. Such a condition is caused by among other factors, the accelerating rice land conversion. The narrower the land managed by farmers, the less harvest produced by farmer household. One of the ways to add additional land to farm is through tenancy. This study aims to understand the effect of land size and ownership on profitability and income. This study uses primary data obtained from interviews with farmers. The data obtained were processed using multiple liniear regession analysis techniques. The results show that there are independent variables that have a positive and significant effect between land size and ownership on profitability and income.